The Role of Middle Class Democratization as a Political Discussion - Mulyati Kartini (Penerbit Hellow Pustaka, 2024)
The existence of an independent middle class is a prerequisite for democracy. In developing countries, including Indonesia, its existence is too strong. Such conditions can be an obstacle to national development towards democratization. The middle class in Indonesia is not a pure middle class as is understood by the middle class in the West, but a traditional society with traditional culture too (paternalistic and always upward orientation, the ties of primordialism are still strong). Therefore, it is very unlikely that the group in question will be able to act as a pure middle class fighting for the interests of the people at large, fighting for the establishment of democracy, who dare to express opinions, have a bargaining position (bargaining position) towards the government, and who are independent.